Medium Voltage Three Phase Static Transfer Switch Operation: Simulation and Modeling - Tahir Mahmood; Muhammad Ahmed Chaudhry (Mehran University Research Journal of Engineering and Technology, 2010)
In this paper, comparison of control logic based on delay logic technique and forced commutation technique for thyristor based three phase medium voltage STS has been made. The developed forced commutation technique for thyristor based STS has broadens the scope of applications in utility distribution network for implementation of different demand side management options. Most importantly, forced commutation technique has shown significant performance for loads having variable power factor. Different point-on-wave with a span of 18° and time duration of 0.001 second has been simulated using delay-logic and forced commutation based control logic techniques. PSCAD/EMTDC software has been used for simulation of different case studies.